HIF-1α-Mediated, NADPH Oxidase-Derived ROS Contributes to Laryngeal Airway Hyperreactivity Induced by Intermittent Hypoxia in Rats - Lin, You Shuei; Shen, Yan-Jhih; Ou, Ping-Hsun; Lai, Ching Jung (Frontiers in Physiology, 2020)
Obstructive sleep apnea, similar to intermittent hypoxia (IH) during sleep, is associated with laryngeal airway hyperreactivity (LAH). IH-induced laryngeal oxidative stress may contribute to LAH, but the underlying mechanism remains unknown. Conscious rats were subjected to repetitive 75 s cycles of IH for 7 or 14 consecutive days. Reflex apneic responses to laryngeal provocations with chemical stimulants were measured to reflect laryngeal reflex reactivity. Compared with control rats, rats exposed to IH for 14 days, but not for 7 days, displayed enhanced apneic response to laryngeal stimulants. The apneic response was totally abolished by perineural capsaicin treatment of superior laryngeal nerves (SLNs) or by the sectioning of the SLNs, suggesting that the reflex was mediated through capsaicin-sensitive SLNs. Daily intraperitoneal administration of N-acetyl-L-cysteine [NAC, a reactive oxygen species (ROS) scavenger], apocynin (an inhibitor of NADPH oxidase) or YC-1 (an inhibitor of HIF-1α), but not their vehicles, largely attenuated this augmented apneic response in 14 day IH rats. Laryngeal lipid peroxidation (an index of oxidative stress) was elevated in 7 day IH rats and 14 day IH rats, and was abolished by any of these three pharmacologic interventions. The protein expression of HIF-1α (an index of HIF-1 activation) and p47phox subunit in the membrane fraction (an index of NADPH oxidase activation) in the laryngeal tissues increased in 14 day IH rats; the former was reduced by NAC, whereas the latter was inhibited by YC-1. These results suggest that 14 days of IH exposure may sensitize capsaicin-sensitive SLNs and result in exaggerated apneic reflex responses to laryngeal stimulants. This phenomenon depends on the action of HIF-1α-mediated, NADPH oxidase-derived ROS.